Strategi Guru Kelas Dalam Membentuk Karakter Peduli Sosial Peserta Didik - Sari, Sugiyanti; Imam, Syafi’I (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
The purpose of this article is to analyze the implementation of classroom teachers in shaping the social awareness of fifth grade students at SDN Sumbernongko Ngusikan Jombang and to analyze the strategies of classroom teachers in shaping the social awareness of fifth grade students at SDN Sumbernongko Ngusikan Jombang. Data collection was carried out by conducting interviews with the principal, classroom teachers, and students. Data was collected through observation, interviews, and documentation. Using a case study approach, data analysis was carried out from the time the research determined the focus of the research to the preparation of the research report. There are three streams in qualitative research analysis activities that occur simultaneously, which include data condensation, data presentation, and conclusion drawing, or what can becalled verification. The results showed that classroom teachers shaped students' social awareness through role modeling, habituation, socialization, and reinforcement. The learning strategies used include direct teaching, cooperative learning, project-based learning, and technology. Supporting and inhibiting factors originate from the family, school, and community environments that influence each other, either through role modeling, positive culture, or mutual cooperation values, and are hampered by a lack of attention, training, and negative environmental influences.